2020
DOI: 10.1039/d0cp00068j
|View full text |Cite
|
Sign up to set email alerts
|

Short-wavelength probes in time-resolved photoelectron spectroscopy: an extended view of the excited state dynamics in acetylacetone

Abstract: Time-resolved photoelectron spectroscopy using a vacuum ultraviolet probe brings new insight to the excited state dynamics operating in acetylacetone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Spectral signatures originating from three different electronic states are indicated. Figure adapted from Kotsina et al 76 to ionization from the hot S 0 ground state -populated from S 1 ( 1 A g ) -are also observed at energies o0.5 eV. This new information revealed by the multi-photon probe step is, however, seen only weakly in the photoelectron spectrum due to the reduced two-photon ionization probability relative to the competing (1 + 1 0 ) scheme.…”
Section: Extending the View Along The Reaction Coordinatementioning
confidence: 72%
See 3 more Smart Citations
“…Spectral signatures originating from three different electronic states are indicated. Figure adapted from Kotsina et al 76 to ionization from the hot S 0 ground state -populated from S 1 ( 1 A g ) -are also observed at energies o0.5 eV. This new information revealed by the multi-photon probe step is, however, seen only weakly in the photoelectron spectrum due to the reduced two-photon ionization probability relative to the competing (1 + 1 0 ) scheme.…”
Section: Extending the View Along The Reaction Coordinatementioning
confidence: 72%
“…Here, we present the basic incorporation of a relatively simple VUV source into our TRPEI spectrometer to convey the advantages of short wavelength probes through a case study on the molecule acetylacetone. 76 This makes use of an established methodology producing the fifth harmonic of a Ti:Sapphire laser (160 nm) in a static gas cell via non-collinear four-wave mixing. 77,78 Such an approach has also been demonstrated previously for use as a probe in other time-resolved studies of non-adiabatic molecular processes, [79][80][81][82] as have related variations employing the sixth harmonic (133 nm) [83][84][85][86] and ninth harmonic (90 nm).…”
Section: Extending the View Along The Reaction Coordinatementioning
confidence: 99%
See 2 more Smart Citations
“…have shown that when probing molecules with states that possess a lifetime shorter than the duration of the laser pulse used to investigate it, one can still observe a signal from this state, but it will be significantly under‐sampled compared to longer‐lived states within the same system. [ 37 , 38 ] This led us to believe that the tall, narrow feature seen in Figure 4 could potentially be due to under‐sampling a very short‐lived state in stilbene oxide. To test this hypothesis, we performed a series of simulations, that are described extensively in the Supporting Information.…”
Section: Discussionmentioning
confidence: 99%